IRON ISOTOPE DIFFERENCES BETWEEN EARTH, MOON, MARS AND VESTA AS POSSIBLE RECORDS OF CONTRASTED ACCRETION MECHANISMS - Poitrasson F.; Halliday A.N.; Lee D.-C.; Levasseur S.; Teutsch N. (My University, 2004)
The iron isotope compositions of Shergotty–Nakhla–Chassigny (SNC) meteorites thought to come from Mars, eucrites and diogenites assumed to sample asteroid 4 Vesta, and rocks from the Moon and Earth have been measured using high precision plasma source mass spectrometry. The means of eight samples from Mars and nine samples from Vesta are within error identical despite a range of rock types. They are lighter by ∼0.1‰ in δ57Fe/54Fe compared to the average of 13 terrestrial mantle-derived rocks. The latter value is identical within uncertainty with a previously published mean of 46 igneous rocks from the Earth. The average for 14 lunar basalts and highland plutonic rocks covering a broad spectrum of major element composition is heavier by ∼0.1‰ in δ57Fe/54Fe relative to our estimate for the Earth's mantle, and therefore ∼0.2‰ heavier than the eucrites, diogenites and SNC meteorites. However, the data scatter somewhat and the Apollo 15 green glass and Apollo 17 orange glass are identical to samples from Mars and Vesta. There is no clear relationship between petrological characteristics and Fe isotope composition despite a wide spectrum of samples. Instead, contrasted planetary isotopic signatures are clearly resolved statistically. After evaluating alternative scenario, it appears that the most plausible explanation for the heavier Fe in the Earth and Moon is that both objects grew via processes that involved partial vaporisation leading to kinetic iron isotope fractionation followed by minor loss. This is consistent with the theory in which the Moon is thought to have originated from a giant impact between the proto-Earth and another planet. Combined with numerical simulations, Fe isotope data can offer the potential to provide constraints on the processes that occurred in planetary accretion.